Resveratrol Pretreatment Improved Heart Recovery Ability of Hyperglycemic Bone Marrow Stem Cells Transplantation in Diabetic Myocardial Infarction by Down-Regulating MicroRNA-34a - Zhang, Fengyun; Wang, Kun; Gao, Fei; Xuan, Yongli; Liu, Xiaohong; Zhang, Zhuoqi (Frontiers in Pharmacology, 2021)
AIM: To examine the effect of resveratrol (RSV) on bone marrow mesenchymal stem cells (BMSCs) under hyperglycemic conditions and on BMSCs transplantation in diabetic rats with myocardial infarction (MI). METHODS: In vitro, BMSCs were isolated from 3-week-old male Sprague Dawley (SD) rats and cultured under hyperglycemic conditions for up to 28 days. Cell viability was analyzed by cell counting kit-8 (CCK-8) assays. The expression of miR-34a was measured by RT-qPCR. Western blotting was used to examine the protein expression of SIRT1, P21, P16, VEGF and HIF-1α. A senescence-associated β-galactosidase assay was used to examine the senescence level of each group. In vivo, a diabetes model was established by feeding rats a high-sugar and high-fat diet for 8 weeks, injecting the animals with streptozotocin (STZ) and continuing high-sugar and high-fat feeding for 4 additional weeks. Then, the MI model was established by left anterior descending coronary artery (LAD) ligation. Each group of rats was transplanted with differentially preconditioned BMSCs after myocardial infarction. Ultrasound was used to analyze cardiac function 1 and 3 weeks after the operation, and frozen heart sections were used for immunohistochemical analysis, Masson staining and CD31 measurement. In addition, ELISA analysis of serum cytokine levels was performed. RESULTS: This study showed that the viability of BMSCs cultured under hyperglycemic conditions was decreased, the cells became senescent, and the expression of miR-34a was significantly increased. Moreover, RSV preconditioning reduced the expression of miR-34a in BMSCs after high glucose stimulation and rejuvenated BMSCs under hyperglycemic conditions. Further analysis showed that the transplantation of RSV-BMSCs improved cardiac function following infarction in diabetic rats, promoted proangiogenic factor release and increased arteriole and capillary densities. CONCLUSION: RSV rejuvenated BMSCs after chronic hyperglycemia-induced senescence by interacting with miR-34a and optimized the therapeutic effect of BMSCs on diabetes with myocardial infarction.